Piety and power: Pious endowments in the Bahrī Mamlūk period, 1250-1382 - Shaaban, Muhammad (AUC Knowledge Fountain, 2016)
The narrative chronicles that document the Mamlūk Empire frequently mention the various pious endowments (sing. waqf, pl. awqāf) of their day. This institution’s importance to the social, political and economic spheres of the Mamlūk Empire is evident by the numerous treatises written about pious endowment and the impressive amount of endowed buildings built from the mid-thirteenth century till the early sixteenth century. This study intends to investigate why this institution became so pervasive during the Bahrī period (648-792 A.H./1250-1382 A.D.) by examining endowed institutions in their entirety. While investigating the endowments of Qalāwūnid sultans, this thesis argues that endowments were consciously employed in order to cultivate legitimacy, power, and patronage networks. Mamlūk pious endowments also provide insights into the land tenure system and power structure that began to change after the third reign of al-Nāṣir Muḥammad b. Qalāwūn (r. 709-41/1310-41). The employment of pious endowments by the Mamlūk elite to realize various goals illustrates the institutions flexibility and its ability to adapt to changing circumstances allowed for the institution’s longevity. These developments and the prevalence of endowments created a precedent for the Burjī Mamlūk period (784-923/1382-1517) which saw the “waqfization” of the land tenure system during the fifteenth century.